R(x)=9x³-2x²+6x+8 y T(x)=3x³+2x²-6x-6; calular R(x)+T(x)
bien explicado porfavor paso a paso gracias
Respuestas
Respuesta dada por:
1
R(x)=9x³-2x²+6x+8 T(x)=3x³+2x²-6x-6
R(x)+T(x)=(9x³-2x²+6x+8)+(3x³+2x²-6x-6) sumamos los terminos semejantes
R(x)+T(x)=(9x³+3x³)+(-2x²+2x²)+(6x-6x)+(8-6)
R(x) + T(x)= 12x³+2
R(x)+T(x)=(9x³-2x²+6x+8)+(3x³+2x²-6x-6) sumamos los terminos semejantes
R(x)+T(x)=(9x³+3x³)+(-2x²+2x²)+(6x-6x)+(8-6)
R(x) + T(x)= 12x³+2
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años